COST-MINIMIZATION OF VILANTEROL / UMECLIDINIUM VERSUS OLODATEROL / TIOTROPIUM IN THE BASIC THERAPY OF SEVERE AND VERY SEVERE COPD - E. G. Kosolapov; F. S. Kochenkov; N. L. Pogudina; D. V. Blinov; N. L. Bondarenko; A. V. Karaulov (IRBIS LLC, 2017)
The recently introduced novel drug combinations for the treatment of COPD are based on long-acting beta-agonists (vilantererol / umeclidinum bromide) and long-acting anticholinergics (olodaterol / tiotropium bromide). In addition to their beneficial clinical effects, these medications have an impact on COPD treatment costs. Minimizing the costs of highly effective medications is necessary to improve the public medical care and drug supply.Objective: to identify the key differences between vilantererol / umeclidinum bromide and olodaterol / tiotropium bromide, and evaluate the ways of minimizing health budget expenditures.Materials and methods. We used the available information from research, clinical trials, and instructions for medical use to conduct a cost analysis that was based on the prices for these medications at different levels of drug supply. As a result, the impact on the healthcare budget was determined under conditions of choosing the least expansive medication and adding vilantererol / umeclidinum bromide in the list of VED.Results. According to the network meta-analysis, when compared with mono-component drugs, vilantererol / umeclidinum bromide showed a more favorable effect on cardiovascular events, as well as a more pronounced effect on the volume of forced exhalation in the first second (FEV1). For the olodaterol / tiotropium bromide combination, no such trend was seen. The costs of 12-month therapy with vilantererol / umeclidinum bromide and with olodaterol / tiotropium bromide were 27,541 and 36,120 rubles, respectively (a difference of 24%). The average direct medical costs were 32,753 and 41,333 rubles per patient per year, respectively. If the vilantererol / umeclidinum bromide combination is added to the VED list and the manufacturer's maximum selling price is registered at the level of the reference countries, the savings can reach 3-5%.Conclusion. In patients with severe and extremely severe COPD, and also when COPD monotherapy in patients without severe symptoms (FEV1 ≥50%, CAT <10 scores, mMRC <2) or with mild to moderate symptoms (FEV1 ≥50%) is not effective, the use of vilantererol / umeclidinum bromide in place of olodaterol / tiotropium bromide is more promising in terms of minimizing health budget spending.